MO811HEALTHY LIFESTYLE SCORE AND MORTALITY IN PATIENTS ON HEMODIALYSIS: AN ANALYSIS OF THE DIET-HD STUDY. (29th May 2021) - Su, Guobin; Saglimbene, Valeria; Wong, Germaine; Ruospo, Marinella; Natale, Patrizia; Craig, Jonathan; Hegbrant, Jörgen; Carrero, Juan Jesus; Strippoli, Giovanni
Abstract: Background and Aims: A healthy lifestyle promotes cardiovascular health and reduces cardiac-related mortality in the general population, but its benefits in patients treated with hemodialysis are uncertain. The aim of this study was to evaluate the association of a modified American Heart Association (AHA) healthy lifestyle score, and its individual components, with all-cause and cardiovascular mortality in a large multinational cohort of patients treated with long-term hemodialysis. Method: Based on the AHA's recommendations for cardiovascular prevention, a modified healthy lifestyle score was derived from non-smoking, being physically active, higher body mass index (BMI, obesity paradox of higher BMI being protective of death in dialysis patients), healthy diet, and well-controlled systolic blood pressure for participants in the DIET-HD study, a multinational cohort study of adults on hemodialysis. Hazard ratios (aHR) were estimated to evaluate the association between the healthy lifestyle score [low (0 -3 points) as the referent, medium (4-6), and high (7-10)] and cardiovascular and all-cause mortality by using cox model. Results: 5483 out of 9757 (56%) patients with complete lifestyle data were followed for a median of 3.8 years (17450.9 person-years). There were 2, 163 deaths, of which 826 cardiovascular-related. Compared with patients with a low lifestyle score (963, 18%), the aHRs (95%CI) for all-cause mortality among those with medium (3, 621, 66%) and high (899, 16%) were 0.70 (0.63-0.78) and 0.57 (0.49-0.66), respectively. Cardiovascular death was 17% [aHR, 0.83 (0.68-0.99] and 30% (0.70, 0.55-0.90) lower in patients with medium and high lifestyle score, respectively. Results were consistent in stratified or complete-case analyses, and after excluding early deaths. Risk reductions were largely driven by being a non-smoker, physically active and having a higher BMI. 20% of deaths were attributed to a medium/low lifestyle score (population attributable fraction; 95% CI 12-28%). Conclusion: A healthier lifestyle, especially non-smoking, regular physical activity, and a higher BMI, is dose-dependently associated with lower all-cause and cardiovascular mortality in hemodialysis patients.